IDENTIFICATION OF DERMATOPHYTA FUNGUS IN BETWEEN THE MEAT SELLER'S TOES WITH TINEA PEDIS AT TERMINAL 42 TRADITIONAL MARKET GORONTALO CITY - ismail mukusibu; Yolan Dunggio; Mindy Eka Astuti (LP2M Universitas Bina Mandiri Gorontalo, 2022)
This study aims to identify the presence of dermatophyte fungi between the Meat Seller's toes with tinea pedis at terminal 42 traditional market Gorontalo City. The type of research used in this study is observational descriptive with a qualitative approach. The sample in this study is all butchers at Terminal 42 Market Gorontalo City which is about 15 samples. The sampling technique used is total sampling technique. Sources of data in this study obtained by data collection techniques, through interviews and examination of fungal culture in the laboratory. The data obtained were analyzed descriptively, which describes the morphological characteristics of dermatophyte fungi based on macroscopic and microscopic observations, and continued with identification activities. Fungal identification is done by match the characteristics of the fungus obtained from the observations with reference to the identification book. The results of the study show based on macroscopic and microscopic examination between the toes of a meat seller with tinea pedis at Terminal 42 Traditional Market Gorontalo City, 53.3% Dermatophytes fungi were found of the samples, namely Trichophyton rubrum. Other than that, 46,7% Non Dermatophyte were also found, such as Aspergillus sp, Rhizopus sp, Candida albicans and species of Metarhizium anisopliaea. Key Words: Fungus, The Toes, Meat Seller, Tinea Pedis